3. Let P(n) be the claim that bn = 7 - 4n for
all integers n0.
P(0) is the statement: b0 = 7 - 4·0.
P(k) is the statement: bk = 7 - 4k.
P(k+1) is the statement: bk+1 = 7 - 4(k+1).
For a proof by induction, you first need to check that the statement P(0) is true. Then assume that P(k) is true and use this to show that P(k + 1) is true.
The statement P(0) is true since we are told in the question that b0 = 7 = 7 - 4·0.
Now assume that the statement P(k) is true. We now need to show that the left-hand side
of P(k+1) is equal to the right-hand side of P(k+1). We are told in the question that bi
= bi-1 - 4 for all integers i1, so we can use that fact.
L.H.S. of P(k+1) | = | bk+1 |
= | bk - 4 |
Use your assumption that the statement P(k) is true to replace the bk in this expression. Your goal is to end up with the right-hand side of P(k+1).